The Relevance of Dewey’s Educational Theory to ‘Teaching and Learning in the 21st Century’ - Yukai Chen (Studies in Social Science & Humanities, 2023)
All of the approaches to education concerned with democracy, John Dewey’s educational theory, circumscribed by his pragmatic, “philosophy of experience”, is arguably the most renowned and revered. This paper offers a detailed description of Dewey’s educational theory, especially his emphasis on educational ideas of inquiry and innovation and children’s creativity and cultivation, which are among the core of his education theory and discusses these two aspects in guiding teaching and learning in the 21th century.